Expansion Characteristics of Stents Used in Congenital Heart Disease: Serial Dilation Offers Improved Expansion Potential Compared to Direct Dilation: Results from a Pediatric Interventional Cardiology Early Career Society (PICES) Investigation. (27th July 2016) - Danon, Saar; Gray, Robert G.; Crystal, Matthew A.; Morgan, Gareth; Gruenstein, Daniel H.; Goldstein, Bryan H.; Gordon, Brent M.
Abstract: Objective: Intravascular stents are now routinely used to treat young patients with vascular stenoses. Future stent redilations are often necessary to account for somatic growth. The purpose of this study was to compile a database of characteristics for stents commonly used in the treatment of congenital heart disease patients, and compare serial dilation to direct dilation to the maximal diameter. Design: A standardized bench testing protocol was established and utilized in the assessment of all stents. Ultra high pressure balloons were used to serially dilate each stent by set increments until the stent reached at least 24 mm in diameter, developed a napkin‐ring configuration, or fractured. Length and diameter of each stent were measured at baseline and following each stage of dilation. Maximal stent diameters, foreshortening properties, and ability to fracture were reported. Stents were then tested for direct dilation from the primary diameter to the maximal diameter, and the same data was obtained. Results: A total of 127 stents were bench‐tested, 80 of which were serially dilated and 47 directly dilated. Most premounted stents could be serially dilated to approximately twice their stated nominal diameter. All tested unmounted stents could be serially dilated to ≥20 mm. Foreshortening occurred at larger diameters, but varied significantly among different stent types. Serial dilation offered more consistent results with significantly less foreshortening and more symmetric expansion when compared with direct dilation. Most premounted stents could be fractured when serially dilated. Conclusions: All tested vascular stents can be dilated beyond their nominal implantation diameter. Serial dilation offers a much more reliable response with uniform expansion, less foreshortening, greater maximal diameter, and improved intentional fracture potential, as compared to direct dilation from the nominal to maximal diameter. In vivo studies are necessary to corroborate these findings in the congenital heart disease population.